The Compatibility of the Statistics and Probability Unit in the Mathematics Books for the Basic Stage in Palestine with the International Standards (NCTM 2014) - Ruba Farouq Hasan Dawoud; Dr. Assumpta Estrada Roca (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study aims to analyze the content of statistics and probabilities in mathematics textbooks in Palestine to find out the extent to which (NCTM 2014) standards have been met for the purpose of developing them. which is a method used in addition to other methods to evaluate the curricula in order to develop them. The study population represented by the content of the statistics and probability units in the mathematics books for the basic stage in Palestine, while the sample of the study is represented by the unit of the statistics and probability unit in the mathematics book of the seventh grade in Palestine.The research results show that the main criterion of mathematical correlation in statistics and probability obtained the highest frequency within the main standards of statistics and probability in mathematics books for the seventh grade, and the main criterion of inference and proof in statistics and probabilities ranked last among the main standards of statistics and probabilities in mathematics books for the seventh grade. Based on the results the researcher recommends which There should be an enhancement of standards for reasoning and proof in the seventh-grade curriculum, this can be achieved by providing more opportunities for critical thinking, building arguments. There is a need to develop standards for mathematical representation in the curriculum to include the use of information and communication technology (ICT) to expand students' representation capabilities and the use of multiple modes such as oral, written, pictorial, and visual.